2018
DOI: 10.1088/2399-6528/aab8df
|View full text |Cite
|
Sign up to set email alerts
|

Activating impurity effect in edge nitrogen-doped chevron graphene nanoribbons

Abstract: Doping has been regarded as one of the most important band structure engineering methods for graphene and its derivatives. Here, we theoretically investigate the chevron-type graphene nanoribbon (CGNR) which is doped by nitrogen in its edges (N-CGNR). The impurity effect can be activated by hydrogen efficiently. When each N atom is adsorbed by a H atom, the σ bond of N induced by selfhybridization is replaced by the N-H sp 2 bond, leaving two p z electrons perpendicular to the CGNR plane. Only one p z electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is found at the edges of the GNRs and causes a rigid downshift of valence (VB) and conduction bands (CB) which has been exploited to create local p-n junctions in GNRs 7,22,38,39 . On the other end, graphitic-N with three bonds to neighboring C atoms and an extra electron partially shared with the π orbitals 37,40 reduces the bandgap and leads to the formation of a new in-gap state localized at the heteroatom. However, the formation of graphitic-N in GNRs remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is found at the edges of the GNRs and causes a rigid downshift of valence (VB) and conduction bands (CB) which has been exploited to create local p-n junctions in GNRs 7,22,38,39 . On the other end, graphitic-N with three bonds to neighboring C atoms and an extra electron partially shared with the π orbitals 37,40 reduces the bandgap and leads to the formation of a new in-gap state localized at the heteroatom. However, the formation of graphitic-N in GNRs remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…While armchair GNRs (aGNR), and in particular 7-aGNR obtained from 10,10′-dibromo-9,9′-bianthracene, represent by far the most studied GNR type, chevron GNRs (cGNRs) based on 6,11-dibromo-1,2,3,4-tetraphenyltriphenylene (precursor 1 , Figure ) have also attracted particular attention. They have been extensively studied experimentally as well as theoretically, , also by considering atomic modifications such as the introduction of heteroatoms or the addition of bulky edge groups. , While most of these studies highlight the interest of GNR as a final product, the on-surface growth process and the different intermediate states, leading to the GNR formation have been only scarcely studied and rarely systematically addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence suggests C-GNRs as promising materials for applications in organic electronics and photovoltaics . Several other works have dealt with the synthesis of C-GNR. Some studies have shown that C-GNRs share interesting properties that arise in different carbon allotropes while presenting other unique features. , Finally, possible applications of C-GNRs in heterojunctions have also already been reported . However, so far, the literature lacks the theoretical description of its electronic and transport properties.…”
Section: Introductionmentioning
confidence: 99%